A new, relictual Antilloides from Mexican caves: First mainland record of the genus and revised placement of the fossil Misionella didicostae (Araneae: Filistatidae) - Fiorini de Magalhaes, Ivan Luiz (2018)
Cave organisms are often relictual, ancient lineages that conserve characters no longer represented in their closest relatives. I here present a new species of Filistatidae from Mexican caves with a notable suite of characters that preclude its placement in any of the filistatid genera currently recorded from North America. A detailed study of its morphology using light and scanning electron microscopy indicates that this is the first mainland species of Antilloides Brescovit, Sánchez-Ruiz & Alayón, 2016 and I describe it as Antilloides chupacabras sp. nov. The genus was previously known only from the Antilles, and its presence in Mexico is evidence of a wider distribution. I here identify some characters which are novel putative synapomorphies of Antilloides, and the phylogenetic affinities of the genus are discussed. Finally, the presence of a modified metatarsus II in males of the new species, among other characters, suggests that the only known fossil filistatid, Misionella didicostae Penney, 2005 from Dominican amber, is misplaced in this genus and the new combination Antilloides didicostae comb. nov. is proposed.